(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The numbers of electric automobiles are quickly increasing. Recharging facilities for electric vehicles are also becoming more frequent. This article examines the present state of rechargeable batteries, charge power levels, including charging techniques for electric cars, as well as their application. There are two types of off-board or on charging systems with or without dual power flow. The use of unidirectional charging reduces the amount of hardware required and simplifies connecting concerns. Battery - based energy injection back to the grid is made possible through bidirectional charging. Since of weight, space, or cost limits, most on-board chargers limit power. To circumvent these issues, they may be incorporated with the electric drive. This paper produces a different phase 230volt off boards charger utilizing CC, CV, or CC-CV charging techniques, as well as simulation results comparing the aforementioned approaches using a 3.2volt, 10AH battery pack in MATLAB.